An experimental study of R-454C pull-down performance as a drop-in refrigerant in a walk-in cold store system. (October 2021) - Mostafa, A.; Hassanain, M.; Elgendy, E.
Highlights: Pull-down performance of R-454C in walk-in cold storeis experimentally investigated. R-454C can replace R-404A in the existing walk-in cold store to complete its life time. Compared to R-404A, compressor power decreases while COP increases using R-454C. Product thermal load has the greatest impact on pull-down time and energy consumption. Abstract: Walk-in cold stores represent the majority of commercial refrigeration applications for product cooling and freezing which make it the highest energy consumer in the sector. The present research aims to assess the pull-down performance of a cold store working with R-454C as a drop-in refrigerant for R404a under different product thermal loads and cooling water temperatures. The product thermal load was changed in a wide range of 0, 450W, 900W and 1350W while the cooling water temperature was changed in range of 27 to 33°C. Experimental results presented that the energy consumption increased approximately four times when the product thermal load increased three times from 450W to 1350W. Moreover, the system COP increases by 20% as the cooling water temperature decreases from 33 to 27°C over the presented cold store temperature. Although the system COP increased by 10.8% after switching to R454C, the system cooling capacity decreased by 12.6% and the energy consumption increased by 20.6%.